Applications of Medium-Chain Triglycerides in Foods - Watanabe, Shinji; Tsujino, Shougo (Frontiers in Nutrition, 2022)
In the 1950s, the production of processed fats and oils from coconut oil was popular in the United States. It became necessary to find uses for the medium-chain fatty acids (MCFAs) that were byproducts of the process, and a production method for medium-chain triglycerides (MCTs) was established. At the time of this development, its use as a non-fattening fat was being studied. In the early days MCFAs included fatty acids ranging from hexanoic acid (C6:0) to dodecanoic acid (C12:0), but today their compositions vary among manufacturers and there seems to be no clear definition. MCFAs are more polar than long-chain fatty acids (LCFAs) because of their shorter chain length, and their hydrolysis and absorption properties differ greatly. These differences in physical properties have led, since the 1960s, to the use of MCTs to improve various lipid absorption disorders and malnutrition. More than half a century has passed since MCTs were first used in the medical field. It has been reported that they not only have properties as an energy source, but also have various physiological effects, such as effects on fat and protein metabolism. The enhancement of fat oxidation through ingestion of MCTs has led to interest in the study of body fat reduction and improvement of endurance during exercise. Recently, MCTs have also been shown to promote protein anabolism and inhibit catabolism, and applied research has been conducted into the prevention of frailty in the elderly. In addition, a relatively large ingestion of MCTs can be partially converted into ketone bodies, which can be used as a component of “ketone diets” in the dietary treatment of patients with intractable epilepsy, or in the nutritional support of terminally ill cancer patients. The possibility of improving cognitive function in dementia patients and mild cognitive impairment is also being studied. Obesity due to over-nutrition and lack of exercise, and frailty due to under-nutrition and aging, are major health issues in today’s society. MCTs have been studied in relation to these concerns. In this paper we will introduce the results of applied research into the use of MCTs by healthy subjects.